Gather evidence on soil and root health challenges in 5 CWANA countries and initiating policy action - CGIAR Research Program on Wheat (2020)
Soil Borne Diseases research focuses on diseases attaching to root systems. Healthy roots store more CO2; reduce negative impacts of climate change. Current national policies do not reflect this.